Moral Message in The Fabel “Ant Struggle” by Aleanzah as A Cultivation Of Peace-Loving Character Education in Junior High School Children - Adinda Erdiana; Nazla Maharani Umaya (Teks: Jurnal Penelitian Bahasa, Sastra, dan Pengajarannya, 2019)
The purpose of this paper is to describe the moral message contained in the label "Perjuangan Semut" by Aleanzah as the planting of character education in junior high school students through literary learning. Based on the Indonesian Ministry of National Education, there are 18 character education instilled in Indonesian citizens, especially students, in an effort to build and strengthen national character. This paper will focus on the 14th character education, namely peace of mind. Peaceful character is an attitude, words and actions that cause other people to feel happy and safe for the presence of peace-loving individuals. Peaceful attitude will make life peaceful and comfortable. The character of peace-loving education can be instilled through literary learning in schools, one of which is through reading fable stories with the theme of peace. The approach used in this study is a qualitative descriptive approach, which is to describe the moral value of peace education in the story of the fable "Ant Struggle" by Aleanzah. While the method used is the content analysis method to find the value of peace-loving character education in the fable. Then, the data in this study are the sentences in the story of the fable that will be analyzed. The data source is a short story written by Aleanzah on the short story page that passed moderation on October 19, 2016.